Cardiomyopathies in children: classification, diagnosis and treatment. Issue 3 (June 2020) - De Angelis, Giulia; Bobbo, Marco; Paldino, Alessia; D'Agata Mottolese, Biancamaria; Altinier, Alessandro; Dal Ferro, Matteo; Merlo, Marco; Sinagra, Gianfranco
Abstract : Purpose of review: Cardiomyopathies are rare in the pediatric population, but significantly impact on morbidity and mortality. The present review aims to provide an overview of cardiomyopathies in children and some practical guidelines for their prognostic stratification and management. Recent findings: Pediatric cardiomyopathies may present as isolated cardiac muscle disease or in the context of complex clinical syndromes. The etiologic characterization represents an important step in the diagnosis and treatment of cardiomyopathies because of its impact on prognosis and on therapeutic measures. Indeed, replacement therapy is nowadays widely available and changes the natural history of the disease. More complex is the management of isolated cardiomyopathies, which lack specific therapies, mainly aimed at symptomatic relief. In this context, heart transplantation shows excellent outcomes in children, but wait-list mortality is still very high. Device therapy for sudden cardiac death prevention and the use of mechanical assist devices are becoming more common in the clinical practice and may help to reduce mortality. Summary: Providing insight into pediatric cardiomyopathies classification helps in the prognostication and management of such diseases. Recent years witnessed a significant improvement in mortality, but future research is still needed to improve quality of life and life expectations in the pediatric population. Abstract : Supplemental Digital Content is available in the text